Delir erkennen in 3 Schritten: vom Screening über die Diagnosesicherung zur Ursachenklärung - Haken, Rebecca von; Hansen, Hans-Christian (Deutsche medizinische Wochenschrift, 2019)
Background Clinicians are commonly confronted with the differential diagnosis of altered mental status, impaired cognition and altered level of consciousness in hospitalized patients including those admitted to medical, geriatric, emergency, intensive and post-operative care units. Although delirium is the most common acute neuropsychiatric condition in the acute hospital setting this diagnosis is commonly delayed, made too late or missed altogether. Difficulties and importance of timely diagnosis The causes of delirious states are manifold. Both, direct damage to the brain tissue as well as encephalopathy as a result of other medical diseases, can be the cause of delirium. Depending on the predisposition delirious syndromes can be provoked by minor medical interventions. Clinical presentation is very variable, but remains largely independent of the triggering mechanisms. Purely catatonic, hypoactive, hyperactive and excitatory types as well as mixed forms can be distinguished. Immediate diagnosis of a delirious syndrome and rapid elucidation of its causes are keys for the implementation of curative therapy. There is a need to act fast because delirious phases are associated with significantly longer hospital stay and increased morbidity as a result of long-term cognitive deficits as well as increased mortality. As negative outcome is closely linked to the duration of a delirious episode, early diagnosis and rapid termination of the delirium constitute a significant positive predictor of outcome. In this respect, delirium represents an emergency, with or without concomitant cerebral or extracerebral symptoms.
Gesehen am 14.01.2020